Synergistic Antimicrobial Effect of Raspberry (Rubus idaeus L., Rosaceae) Preparations and Probiotic Bacteria on Enteric Pathogens - Justyna Bauza-Kaszewska; Ewa Żary-Sikorska; Andrzej Gugolek; Anna Ligocka; Monika Kosmala; Elżbieta Karlińska; Bartosz Fotschki; Jerzy Juśkiewicz (Polish Journal of Food and Nutrition Sciences)
Due to the increasing microbial tolerance to commonly used food preservatives, as well as growing consumer awareness of their adverse impact on human health, alternative methods of pathogens reduction in food are widely investigated. The aim of this research was to examine the antimicrobial activity of red raspberry pomace and seed preparations against enterohemorrhagic Escherichia coli (EHEC), Salmonella Typhimurium, Salmonella Enteritidis, Listeria monocytogenes , and probiotic Lactobacillus rhamnosus strain. The combined action of LAB (lactic acid bacteria) and raspberry preparations on the pathogenic species was also evaluated. The results of our study showed no or weak antibacterial effect of raspberry preparations on the pathogenic bacteria tested. Regardless of preparation concentration (1.0 or 2.0 mg/mL), the bacteria number after 48-h incubation was usually higher than in the culture at the initial stage and varied from 10 5 to 10 7 cfu/mL. On the other hand, probiotic Lactobacillus rhamnosus strain caused a significant reduction in the enteric pathogen count after 24-h co-culture with LAB. The concentrations of both Salmonella serotypes were below the detection limit of the analytical methods applied. Moreover, the combined use of LAB and raspberry preparations resulted in the total elimination of Salmonella strains and the reduction in L. monocytogenes number from 10 5 to 10 2 -10 4 cfu/mL after 24-h co-culture. EHEC revealed the highest resistance to the mixed culture effect. The synergic antimicrobial effect suggests the possibility of applying probiotic bacteria and berry preparations as natural antimicrobial agents in the food industry.